OPTIMALISASI KEAMANAN JARINGAN WIFI DI LINGKUNGAN KAMPUS MELALUI IMPLEMENTASI WPA3 - Pakaya, Roys; Giu, Jamal Darusalam (Journal Of Software Engineering And Communication, 2025)
The development of digital technology in the campus environment requires the availability of fast, stable, and secure WiFi networks. However, threats to wireless network security are increasing, ranging from data theft to unauthorized access. This study aims to evaluate the effectiveness of WPA3 implementation in enhancing Wi-Fi network security in a campus environment. The research employed a quantitative method with an experimental approach, comparing Wi-Fi network configurations using WPA2 and WPA3 security protocols. Data were collected through penetration testing using Kali Linux and Metasploit, as well as network performance analysis using Wireshark and iPerf. Penetration testing results showed that the WPA3 network is more resistant to dictionary attacks and KRACK attacks compared to the WPA2 network. Network performance analysis indicated that WPA3 implementation does not significantly affect network throughput and latency, but there was a slight improvement in network stability with reduced packet loss. The results of this study indicate that WPA3 offers a significant improvement in security without significantly sacrificing network performance. It is recommended to implement WPA3 to improve Wi-Fi network security in a campus environment. This study implies that WPA3 can be implemented as a better security solution for Wi-Fi networks in various educational institutions.